Controlling infestation of a chocolate factory by Plodia interpunctella by combining mating disruption and the parasitoid Habrobracon hebetor. (13th May 2016) - Trematerra, Pasquale; Oliviero, Annachiara; Savoldelli, Sara; Schöller, Matthias
Abstract: A field experiment of 4 years' duration was carried out to evaluate the efficacy of combining the mating disruption (MD) formulation Dismate ZETA ((9 Z, 12 E )‐tetradecadienyl acetate), with the parasitoid Habrobracon hebetor against the Indianmeal moth Plodia interpunctella in a chocolate factory. The experimental period began early in 2011 and ended in late 2014. Begane Dismate dispensers were placed in the facility from 2011 to 2014 and H. hebetor was released in 2014. Pheromone‐baited traps were used to monitor the flight activity of the male moths and oviposition Petri dish traps were placed to assess the progeny production of P. interpunctella females. Following the start of MD, a decrease in the number of P. interpunctella males caught in monitoring traps was observed from 2011 to 2013. A further decline in the moth population was noted in 2014, when MD was combined with the release of parasitoids. The presence of larvae in the oviposition cups was occasionally observed throughout the monitoring period, from 2011 to 2014. This study demonstrates that the combined system of MD and parasitoids is an effective and reliable technique that can be used to successfully control P. interpunctella .